2006
DOI: 10.1111/j.1365-2478.2006.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground viscosity and stiffness measurements for near surface seismic velocity

Abstract: A B S T R A C TIn land surveys, the weathering layer can often distort the seismic signal due to it passing through rapid velocity and density changes, dispersion, scattering and inelastic absorption. In a simple spring-dashpot model for the earth response, an equivalent medium groups these complex phenomena into two parameters only; these are called ground viscosity and ground stiffness. The most recent controllers for vibrators can estimate both parameters. To validate these measurements, Saudi Aramco conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Recent uphole measurements elsewhere in the Arabian Peninsula showed that seasonal variations may cause shallow velocity changes up to 400 m/s. A similar dependence was observed by Ley et al (2006) while processing vibrator-plate attributes. Interpreting a variogram like this one, in order to choose an optimal range for kriging, is often quite questionable.…”
Section: F I R S T C a S E H I S T O Rysupporting
confidence: 78%
“…Recent uphole measurements elsewhere in the Arabian Peninsula showed that seasonal variations may cause shallow velocity changes up to 400 m/s. A similar dependence was observed by Ley et al (2006) while processing vibrator-plate attributes. Interpreting a variogram like this one, in order to choose an optimal range for kriging, is often quite questionable.…”
Section: F I R S T C a S E H I S T O Rysupporting
confidence: 78%
“…Strong wave field distortions give rise to amplitude changes, time shifts, and scattered noise degrading the seismic image quality. This so-called near-surface problem has been recognized since the early days of seismic exploration [6]- [11]. Fig.…”
Section: Near-surface Problem Inmentioning
confidence: 99%
“…The basic idea of exploiting the vibrator plate response dates back to the 80's, introduced by the pioneering papers of Lerwill (1981) and Sallas (1984), but only more recently Ali et al (2003) and Ley et al (2006) applied it on a larger scale, validating its practical value. The Earth response is approximated by a simple model composed of a spring and a dash-pot in parallel, characterized by a stiffness and viscosity factor, respectively.…”
Section: Vibrator Platementioning
confidence: 99%
“…Indeed, this approach overcomes only partially the problem affecting refraction statics, i.e., the so-called Љhidden layer(s)Љ, while it works optimally when lateral and vertical velocity variations are mild. When lateral changes are sharp instead, other recent methods can be used and are reviewed in this paper: for example, the integration of remote sensing in the near-surface modelling (Vesnaver et al 2009), and the use of geostatistics (co-kriging) for extracting information from the Vibroseis response, such as the stiffness and viscosity of the ground (Ley et al 2006).…”
Section: Introductionmentioning
confidence: 99%